Treachery trail - Farrell, Cliff (Doubleday & Co Garden City, New York, 1969)
"This is the story of violent events and treacherous deeds ... of a man who could not escape the shadows of his past .... Val Lang was a man on the run. For eight years he painstakingly covered his tracks; for eight years he tried to forget that he had been accused of shooting his best friend, Boone Irons, in the back--that Boone's father, Cass, had sworn to see him hang for it. Behind a shaggy black beard and an assumed name Val finally settled in the Wyoming Territory. He was a shrewd cattleman and his ranch prospered--but he could not shake the fear that someday Cass Irons would come for him. Val was right. The day the old man and his crew rode into town it began again--the running, the hiding. But this time both the pursued and the pursuers were riding toward violent death."--Dust jacket
35409
Keywords: Western; Frontier and pioneer life; Revenge; Vengeance